Snake Antivenoms—Toward Better Understanding of the Administration Route - Erika Gamulin; Sanja Mateljak Lukačević; Beata Halassy; Tihana Kurtović (Toxins, 2023)
Envenomations induced by animal bites and stings constitute a significant public health burden. Even though a standardized protocol does not exist, parenterally administered polyclonal antivenoms remain the mainstay in snakebite therapy. There is a prevailing opinion that their application by the i.m. route has poor efficacy and that i.v. administration should preferentially be chosen in order to achieve better accomplishment of the antivenom therapeutic activity. Recently, it has been demonstrated that neutralization not only in the systemic circulation but also in the lymphatic system might be of great importance for the clinical outcome since it represents another relevant body compartment through which the absorption of the venom components occurs. In this review, the present-day and summarized knowledge of the laboratory and clinical findings on the i.v. and i.m. routes of antivenom administration is provided, with a special emphasis on the contribution of the lymphatic system to the process of venom elimination. Until now, antivenom-mediated neutralization has not yet been discussed in the context of the synergistic action of both blood and lymph. A current viewpoint might help to improve the comprehension of the venom/antivenom pharmacokinetics and the optimal approach for drug application. There is a great need for additional dependable, practical, well-designed studies, as well as more practice-related experience reports. As a result, opportunities for resolving long-standing disputes over choosing one therapeutic principle over another might be created, improving the safety and effectiveness of snakebite management.